Trends in adolescent and adult vaccination in pharmacy and medical settings in the United States, 2018–2024: a database study - Yi Zheng; Dong Wang; Ya-Ting Chen; Kunal Saxena; Goran Bencina; Amanda L. Eiden (Expert Review of Vaccines)
Background Pharmacies can increase access to vaccines. This study aimed to describe trends in the proportion of adolescent and adult vaccinations administered in pharmacies in the United States from 2018 to 2024.Research design and methods This was a retrospective cross-sectional analysis of medical and pharmacy claims from commercial health insurance enrollees. We recorded vaccinations received by enrollees ≥9 years of age from 2018 to 2023 (routine vaccines) or 2024 (seasonal vaccines). We calculated the annual proportion of vaccinations occurring in pharmacies and the accumulated percent change in vaccination rate during each year from 2020 onward compared to 2018–2019.Results The proportion of routine vaccinations occurring in pharmacies was higher among adults than among adolescents. For most routine vaccines, this proportion increased during the study period. The lowest proportion was observed for adolescent human papillomavirus vaccination in 2018 (0.2%), and the highest for herpes zoster vaccination among adults ≥65 years of age in 2023 (88.6%). For all age groups, pharmacy-based vaccination was more common for seasonal influenza and SARS-CoV-2 vaccines than for all routine vaccines except herpes zoster.Conclusions Pharmacy-based vaccination is increasingly common in the United States, particularly among adults and for seasonal vaccines, and can help increase the overall level of vaccine uptake.